Synthesis, Characterization, and Antibacterial Activity of ZnO-CuO Nanoparticles Embedded in Chitosan and Polyvinyl Alcohol as Supporting Materials - Ahmad Fatoni; Marcelina Putriani; Amar Mulya Lubis; Mauizatul Hasanah; Ensiwi Munarsih; Nurlisa Hidayati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
The biosynthesis of bimetallic metal nanoparticles (ZnO–CuO) and their interaction with chitosan and polyvinyl alcohol (PVA) have garnered significant attention in recent years, primarily due to their promising antibacterial applications. This work proposes the bio-fabrication of ZnO–CuO nanoparticles, chitosan–PVA–ZnO–CuO nanoparticle films, and reports their physicochemical and antibacterial potential. Green betel leaves (Piper betle L.) ethanol extract was used to synthesize ZnO–CuO nanoparticles. For as-prepared bimetallic NPs, chitosan (CS), PVA, and bimetallic NPs-based films were fabricated using the casting technique. The films were investigated by Fourier Transform Infrared (FT-IR) spectroscopy, X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and the antibacterial activity was evaluated by the agar diffusion method. FT-IR measurements showed the presence of Zn–O and Cu–O functional groups at 396 cm⁻¹ and 418 cm⁻¹ in the nanoparticles, and the films A, B, and C, these bands were observed at 394–395 cm⁻¹ (Zn–O) and 409–416 cm⁻¹ (Cu–O). Crystallite sizes of ZnO, CuO, and ZnO–CuO NPs were 4.845 nm, 54.143 nm, and 5.306 nm, respectively. SEM examination showed that the surface of the films was rough and not homogeneous. Antibacterial experiments revealed the better inhibitory activity of film C than film A and film B. The advantage of the antibacterial property was attributed to the reactive oxygen species (ROS) generated by the ZnO–CuO in collaboration with chitosan. These results indicate that chitosan/PVA film loaded with ZnO–CuO NPs holds great promise as an effective antibacterial packaging material.